The interrogation of Ashala Wolf - Kwaymullina, Ambelin, 1975- (Kwaymullina, Ambelin, 1975- Tribe, 2014)
Taking refuge among other teens who are in hiding from a government threatened by their supernatural powers, Ashala covertly practices her abilities only to be captured and interrogated for information about the location of her friends.